Comparison of Mastectomy Surgery under Total Intravenous Anaesthesia (Tiva) Versus General Anaesthesia (The Planet, 2023)
Mastectomy surgery can be done under different anaesthetic techniques. We compared general anaesthesia versus total intravenous anaesthesia for mastectomy on 53 randomly assigned patients from January 2020 to january 2021 to observe the efficacy of TIVA. Fifty three such elective surgical patients of age group (30-65 years) having American Society of Anaesthesiologist (ASA) physical status I & II were randomly assigned to one of the two groups. Group-I (n-25) patients received general anaesthesia (intravenous anaesthetic agent, inhalational anaesthetic agent, narcotic and muscle relaxant) Group-II (n-28) patients received total intravenous anaesthesia (ketamine, propofol,narcotic,NSAID). Haemodynamic parameter i.e. mean blood pressure and heart rate were recorded preoperatively and per operatively. Patient’s pain experience was evaluated by visual analogue scale post operatively. There were no significant (p>.01) changes in haemodynamic parameter in both the groups. Pain evaluation by visual analogue scale was also negative. This study showed that TIVA for Mastectomy surgery is safe, cost effective and environmental friendly.
Keywords: Mastectomy Surgery; Intravenous Anaesthesia; General Anaesthesia